Istoria literară şi provocările actualităţii. modele, teorii, practici discursive - Antonio Patraş (Revista de Istorie și Teorie Literară)
The present essay endeavours to illustrate a few of the most characteristic methods of inquiry into the literary phenomenon, by working on the current distinction between literary criticism (which is supposed to be synchronous) and literary history (implicitly, a diachronic approach). Another necessary discrimination appears to be the one between literary history – perceived as fundamental among all subjects of study, and the history of literature that is nothing less than an ordinary branch of literary history, the latter comprising a larger and more diversified range of approaches.